POLYPHARMACY IN AGEING POPULATIONS: NEUROLOGICAL RISKS, HEALTHCARE DETERMINANTS AND DIGITAL INTERVENTIONS IN EUROPE - Paulina Prudzic; Weronika Winiarska; Wiktoria Bełcikowska-Skowron; Aleksandra Siegmund; Marzena Chrapczyńska; Agnieszka Filarecka; Piotr Przybyszewski; Emilia Przybyszewska; Martyna Sienicka; Julia Gatniejewska (International Journal of Innovative Technologies in Social Science, 2026)
As Europe’s population ages, managing polypharmacy has evolved from an individual clinical concern into a major public health priority [3, 4]. Broadly driven by multi-organ chronic diseases and uncoordinated specialist care, the accumulation of multiple drug prescriptions generates heavy clinical and economic costs [5, 6]. This narrative review maps the neurological risks linked to polypharmacy and evaluates the structural healthcare factors that shape prescribing habits across European nations [1, 12]. Gathering data published between 2010 and 2024, we synthesized evidence regarding regional prevalence, cumulative anticholinergic burden, and system-level weaknesses [4, 14]. Current statistics reveal that 40–50% of older Europeans aged ≥ 65 years face polypharmacy, though rates differ widely between countries [4, 24]. The central nervous system bears a disproportionate share of drug-induced harm; common outcomes include accelerated cognitive decline, acute delirium, motor instabilities, and the worsening of pre-existing psychiatric or epileptic conditions [13, 14, 19]. Much of this damage stems directly from an unmonitored anticholinergic burden, which tracks closely with elevated dementia rates and mortality [15, 16]. At the institutional level, fragmented communication between physicians, poor access to comprehensive geriatric assessments, and the absence of routine medication reviews act as primary drivers of unsafe prescribing [2, 26]. Mitigating these risks requires integrating targeted organizational shifts—such as mandatory deprescribing protocols and clinical pharmacist oversight—with digital infrastructure, including artificial intelligence platforms and clinical decision-support software [7, 31, 33, 34].